AB0395 Subcutaneous tocilizumab as monotherapy or in combination with a csdmard in patients with rheumatoid arthritis: 24 weeks results of the french phase iiib study, "tosca". (15th June 2017) - Fautrel, B; Senbel, E; Vittecoq, O; Rist, S; Combe, B; Schaeverbeke, T; Lioté, F; Flipo, R-M; Baffie, C; Pau, D; Fraga, E Condé Da Silva; Pinta, A; et al.
Abstract : Background: After the two global pivotal studies, which evaluated the safety and efficacy of subcutaneous tocilizumab (TCZ-SC) in combination (combo) with conventional synthetic disease-modifying antirheumatic drugs (csDMARDs), it was important to understand the efficacy and safety profile of TCZ-SC both as monotherapy (mono) and in combo with csDMARDs in patients (pts) managed in conditions less strict than those of pivotal clinical trials. Objectives: To evaluate the efficacy and safety of TCZ-SC 162 mg once weekly (qw) as mono and in combo with csDMARDs over 24 weeks in adult pts with moderate to severe RA. The primary efficacy criterion was the change in DAS28-ESR from baseline to week 24 (W24). Methods: TOSCA is a national, multicenter, open-label phase IIIb study, part of the international umbrella study (TOZURA). It aimed to enroll TCZ-naïve pts who were csdMARDs inadequate responders (IR) and/or biological DMARD-IR. Pts received TCZ-SC 162 mg qw for 24 weeks, administered at the investigator's discretion as mono or in combo with a csDMARD. Stable oral corticosteroids (CCS), ≤10 mg/day prednisone or equivalent (eq.pred), were allowed. Results: The baseline characteristics of the 139 included patients were: mean age 57.3 years (±13.8), 74.1% female, mean RA disease duration 10.8 years (±9.2), immunopositivity 85.5%, structural joint damage 65.6%, mean DAS28 5.8 (±1.1). 52.5% of patients were bDMARD-IR. TCZ-SC was initiated in mono TCZ in 30.9% of pts and in combo in 69.1% (79.1% MTX). Oral CCS were used by 56.8% of pts (mean 7.4 mg/d/eq.pred.±2.7). In comparison with combo pts, the mono pts were older (58.7 vs 56.7 years), with a higher mean DAS28 (6.1 vs 5.7), a longer disease duration (11.5 vs 10.6 years), and a higher CCS mean dose (8.3 vs 6.9 mg/d/eq.pred.). At W24, the mean DAS28 score variation vs baseline was -3.1 overall (p<0.0001); -3.0 in mono TCZ vs -3.1 in combo TCZ (p=0.76) (Fig.). The proportion of pts who achieved DAS28 remission was 51.1% (41.9% in mono vs 55.2% in combo (p=0.14)). CDAI remission, which does not include acute phase reactants, was achieved in 17% pts, 16% in mono vs 17% in combo (p=0.95). At W24, 27.9% of pts receiving >5 mg CCS at baseline decreased the daily dose ≤5 mg/d/eq.pred. (30.1% in mono TCZ and 26.7% in combo). Out of the 23 pts (16.5%) who withdrew, 13.0% did so for lack of efficacy and 52.1% for safety reasons; one death occurred following a septic shock after surgery for gastric volvulus, not related to TCZ. At W24 95.7% of patients had experienced at least one adverse event (AE) and 10.1% at least one serious AE with similar rates between groups. Conclusions: TCZ-SC demonstrated at 6 months comparable efficacy, safety and steroid sparing results in mono- and combo therapy consistent with the known profile of TCZ-IV. Disclosure of Interest: B. Fautrel: None declared, E. Senbel: None declared, O. Vittecoq: None declared, S. Rist: None declared, B. Combe: None declared, T. Schaeverbeke: None declared, F. Lioté: None declared, R.-M. Flipo: None declared, C. Baffie Employee of: Altizem on behalf of Roche, D. Pau Employee of: Roche, E. Condé Da Silva Fraga Employee of: Roche, A. Pinta Employee of: Roche, P. Gaudin: None declared